Double shadow - Ludington, Andrew (Splinter effect, 2026)
"In this thrilling installment of the Splinter Effect series, time-traveling archaeologist Rabbit Ward returns to the past to help save his former adversary and track down a murderous thief in first century Jerusalem. ROME, 2019. Time-traveling, Smithsonian archaeologist Rabbit Ward is back in the present, but not for long. Helen, his former adversary and growing ally, is in trouble with the law after being framed for a murder she didn't commit. Stuck in hiding and running out of other options, she turns to Rabbit for help. "Help" in this case involves a trip to first century Jerusalem to track down a mysterious man named Einar Eshek. But Rabbit won't have to do this mission alone; as soon as he arrives in 68 CE, he meets a younger version of Helen, one who has never met him before. Together, they work to track down Eshek, who turns out to be not only a time-traveling thief, but a murderous psychopath. As they pursue Eshek through time, Rabbit and Helen feel something even bigger pulling them together. Torn between the two versions of the woman he knows, and with the clock ticking down on Helen's fate in 2019, Rabbit might have no choice but to betray her past self to secure Helen's safety in the future. Tensions rise as Jerusalem prepares to go to war with Rome, and Rabbit races to capture Eshek, clear Helen's name, and make it back to 2019 in one piece-a feat that's proving to be easier said than done-before everything falls apart"-- Provided by publisher.